ANALYZING FINANCIAL LITERACY AND SOCIO-ECONOMIC EMPOWERMENT AMONG RURAL WOMEN IN TAMIL NADU (CAHIERS MAGELLANES-NS, 2024)
This study evaluates the impact of financial literacy on economic empowerment and social inclusion for women in rural India. With a focus on the unique challenges faced by rural women, the research investigates how increased financial knowledge influences their economic activities, financial independence, and social integration. Employing a mixed-methods approach, the study integrates quantitative data from surveys and qualitative insights from interviews conducted with women in various rural communities. The findings reveal that financial literacy significantly enhances women’s ability to manage finances, make informed economic decisions, and participate more fully in social and community activities. Key benefits identified include improved budgeting skills, increased confidence in financial matters, and greater access to financial resources. This research highlights the critical role of tailored financial education programs in fostering economic and social advancement in rural settings. The study provides actionable recommendations for policymakers, NGOs, and educational institutions to develop and implement effective financial literacy initiatives aimed at empowering rural women.